Ramona the pest eaudiobook - Cleary, Beverly (Ramona Quimby, 2010)
Newbery Medal-winning author Beverly Cleary expertly depicts the trials and triumphs of growing up through a relatable heroine who isn't afraid to be exactly who she is. Ramona Quimby is excited to start kindergarten. No longer does she have to watch her older sister, Beezus, ride the bus to school with all the big kids. She's finally old enough to take the bus too! Then she gets into trouble for pulling her classmate's boingy curls during recess. Even worse, her crush rejects her in front of everyone. Beezus says Ramona needs to quit being a pest, but how can she stop if she never was trying to be one in the first place? The classic Ramona books continue to make young readers laugh in recognition and pleasure. They're perfect for independent and shared reading, at home or in the classroom.